The regulation of the global water services market / edited by Julien Chaisse ; foreword by Laurence Boisson De Chazournes. - Chaisse, Julien (Cambridge University Press, 2017)
Drinking water and wastewater services must be provided to many sectors of a nation's economy, including its industrial, commercial, and residential sectors. This forms the scope of the water industry's activities and it explains why the privatisation of water sanitation and water services has become a huge market and a much-debated issue in a number of jurisdictions. Historically the water industry has been run as a public service which is owned by the local or national government, recent trends suggest that the role of the private sector is increasing. The growing economic interests concerning water and wastewater services are generating a tension with the recent recognition of the human right to water and sanitation. This tension between human right and economic rules is the focus of this book, which reviews all the international rules that form the regulation of global water services.